2017
DOI: 10.13048/jkm.17016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Skin Lipid Barrier Formation on Hataedock Treatment with Douchi

Abstract: Hataedock is indigenous treatment of Korean medicine that administers herbal extracts orally to newborn infants for remove the fetal heat. The purpose of this study was to evaluate skin lipid barrier formation effect of Hataedock treatment with Douchi. Methods: We measured the Western blot to observe the expression of protein such as involucrin and loricrin. Moreover, we observed immunohistochemical changes in NC/Nga mice. The 3-week-old NC/Nga mice were divided into 3 groups: the 3-week-old control group (3w-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Our previous studies have shown that HTD mitigates AD development due to fetal heat and controls 2skewed conditions [26,27]. Moreover, our studies showed that lipid barrier formation in the epidermis is increased after the application of HTD [28].…”
Section: Introductionsupporting
confidence: 54%
“…Our previous studies have shown that HTD mitigates AD development due to fetal heat and controls 2skewed conditions [26,27]. Moreover, our studies showed that lipid barrier formation in the epidermis is increased after the application of HTD [28].…”
Section: Introductionsupporting
confidence: 54%
“…In previous studies, we demonstrated that HTD treatments reduce the inflammatory response by down-regulating Th2 differentiation 48) . In addition, we demonstrated that HTD treatments maintains and fortifies the lipid barrier 11) . Based on these results, we hypothesize that HTD could attenuate AD symptoms…”
Section: Discussionmentioning
confidence: 72%
“…This trend results from mixing of states in lead due to orbital angular momentum, which results in a paramagnetic term in the Ramsey equation (187). Consequently, the 207 Pb resonance shifts downfield as donor atoms are changed from oxygen to nitrogen to sulfur (Table IV) (39,178,181,182,(188)(189)(190). Although the Pb(II) 6s lone pair of electrons is expected to also have a profound effect on the 207 Pb chemical shift, only one report to date addresses this question.…”
Section: Lead-207 Parameters: Chemical Shifts and Coupling Constantsmentioning
confidence: 99%